Determinants of anemia in young women in middle school - Parti Parti; Eki Nawang Wulandari (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2018)
Anemia and sttunting are health problems with multiple causes, namely nutriton (vitamin and mineral deficiency) and nutritional (infectious diseases). This problem not only occurs in pregnant women but also in infancy, toddiers, school children and even teenagers. one of the causes of problems occuring in efforts to improve nutritional status in jeneponto. regency is the high rate of nutritional anemia due to lack of iron. This study aims to analyze teh most influential factors on the incidence of anemia against stunitng events in young women aged 13-15 years. Design of case control research with the number of samples 186 people, sampling technique by way of totaling sampling. Bivariate analysis is used to determine what factors are related to the incidence of anemia. multivariate analysisis were used to look at the factors that most affected the incidence of anema. The results showed that the most determinant of the anemia was (1) menstrual cycle p - 0,032 OR 1,61 (CI 95% 1,069 - 2,433) and menstrual periode p=0,001 OR=2,24 (CI 95% 1,528-3,283), (2) intake nutrient p=0,03 OR=2,64 (CI 95% 0,904-7,701) and level of education mather p=0,002 OR= 4,08 (CI 95% 1,366-12,224). It is expected that eating behavior with a balanced nutrition pattern should be amphasized through school health education programs.